A Value-Based Islamic Education Management Model: A Case Study of Love-Based Curriculum Implementation in Developing Humanistic School Culture - Djoko Susilo; Khairil Anwar; Mowafg Abrahem Masuwd (MASI Mandiri Edukasi, 2026)
This study examines how a love-based curriculum is institutionalized within Islamic education management to develop a humanistic school culture. The research addresses the persistent gap between value-based educational leadership discourse and its practical implementation in institutional management, particularly in faith-based schooling contexts. This research employed a qualitative interpretive case study design conducted at MAN Kotawaringin Timur, Indonesia. Data were collected from 24 participants, including school leaders, teachers, staff members, students, and a school committee representative, through in-depth interviews, participatory observations, and analysis of institutional documents. Data were analyzed using iterative thematic coding to identify patterns of value integration across management practices. The findings reveal that the love-based curriculum functions not only as a pedagogical approach but also as an organizational governance framework embedded in four interconnected managerial dimensions: value-oriented strategic planning, empathetic-participatory leadership, dialogical learning practices, and continuous character-oriented evaluation. These dimensions collectively form an integrative Islamic education management model that transforms ethical values into institutional drivers shaping relational trust, psychological safety, and student social-religious engagement. Theoretically, this study contributes to value-based educational leadership and school culture research by conceptualizing love as an institutional governance mechanism within Islamic educational management.